Dipcoating of Poly (E-caprolactone)/hydroxyapatite Composite Coating on Ti6Al4V for Enhanced Corrosion Protection - Mas Ayu, Hassan; Mohd Faiz, Mohd Yusoff; Mohammed Rafiq, Abdul Kadir; Nida, Iqbal; Rafaqat, Hussain (Elsevier, 2014)
Surface modification of metallic implants is often required to facilitate positive interaction between the implant and the surrounding hard tissue. In the present study, a polymer-ceramic composite coating of poly (Îµ-caprolactone)/hydroxyapatite (PCL/HA) was successfully deposited on a Ti6Al4V substrate by dip coating technique in chloroform suspension at room temperature. The influence of PCL concentration and dip coating parameters was studied and the process parameters were optimized to obtain a homogeneous, crack free, densely packed and adhesive coating. The surface of coating was rough and contained surface level pores, which are necessary for ingrowth of osseous tissue. The corrosion behaviour of the coated substrates was investigated by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS), the results of which showed that the composite coating of PCL/HA substantially enhanced the corrosion resistance of Ti6Al4V alloy.